2008
DOI: 10.1007/s10803-008-0584-4
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Sleep Characteristics, EEG Abnormalities and Epilepsy in Developmentally Regressed and Non-regressed Children with Autism

Abstract: This study investigated sleep of children with autism and developmental regression and the possible relationship with epilepsy and epileptiform abnormalities. Participants were 104 children with autism (70 non-regressed, 34 regressed) and 162 typically developing children (TD). Results suggested that the regressed group had higher incidence of circadian rhythm disorders than non-regressed children. The regressed group showed higher Children's Sleep Habits Questionnaire Bedtime Resistance, Sleep Onset Delay, Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 66 publications
(91 reference statements)
5
92
2
1
Order By: Relevance
“…Seizures were present for 19% of our language regression sample, which falls between 7% (Baird et al 2008) and 31.3% (Kobayashi and Murata 1998) reported in the literature. The rate of seizures in our language delay group was 6%, which was somewhat lower than that reported for other no regression groups, e.g., 11% (Hansen et al 2008) to 15% (Giannotti et al 2008;Kobayashi and Murata). Overall, our regression group seems similar to others described within the literature.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Seizures were present for 19% of our language regression sample, which falls between 7% (Baird et al 2008) and 31.3% (Kobayashi and Murata 1998) reported in the literature. The rate of seizures in our language delay group was 6%, which was somewhat lower than that reported for other no regression groups, e.g., 11% (Hansen et al 2008) to 15% (Giannotti et al 2008;Kobayashi and Murata). Overall, our regression group seems similar to others described within the literature.…”
Section: Discussionsupporting
confidence: 71%
“…Baird et al (2008) found similar symptom severity for children with autism across language regression groups; however, children with broad ASD diagnoses showed greater symptom severity in the presence of some language regression versus no regression. Giannotti et al (2008) found that children with regression demonstrated greater autism severity when compared to non-regression counterparts as measured by the Childhood Autism Rating Scale (37.50 vs. 41.50). Although few differences were noted between regression and non-regression groups, Werner et al (2005) and Richler et al (2006) found social reciprocity to be more impaired for children with regression versus non-regressed comparison groups.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to an increased prevalence of epilepsy in individuals with ASD, there is also a marked increased incidence of epileptiform activity on the EEGs of people with ASD (Giovanardi et al 2000;Hrdlicka et al 2004;Canitano et al 2005;Gabis et al 2005;Hughes and Melyn 2005;Baird et al 2006;Chez et al 2006;Kim et al 2006;Akshoomoff et al 2007;Hara 2007;Parmeggiani et al 2007;Giannotti et al 2008;Spence and Schneider 2009). Whereas interictal spikes occur in .5% of normally developing children without a history of epilepsy (EegOlofsson et al 1971), more recent studies have shown that up to 60% of EEG records from children with ASD have interictal spikes (Hughes and Melyn 2005) and many of the children with abnormal EEGs do not have a history of epilepsy (Hughes et al 2015).…”
Section: Prevalence Of Comorbid Autism and Epilepsymentioning
confidence: 99%
“…Developmental regression appears less clear in its relationship to autism and epilepsy with mixed findings. Several groups have reported a higher frequency of seizures/epilepsy in ASD with regression versus no regression (Hrdlicka et al 2005;Giannotti et al 2008). In contrast, a series of studies has demonstrated that rates of epilepsy/seizures do not differ significantly in ASD individuals with regression versus no regression (Canitano et al 2005;Baird et al 2008;Hansen et al 2008).…”
Section: Introductionmentioning
confidence: 97%